Relationship between Physical Changes and Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis at Royal Prima Medan General Hospital in 2024 - Nidia Felisia Halawa; Frisandia Gulo; Raka Dwi Anugrah; Creasy Dervin Br Pangaribuan; Ranila Buulolo; Tiarnida Nababan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Chronic Kidney Disease (CKD) is a condition that gradually and irreversibly changes the role of the kidneys, resulting in elevated urea and electrolytes and the inability of the body to maintain fluid and electrolyte balance. Hemodialysis (HD) is an effective therapy for kidney failure disease. Physical changes will inevitably occur in CKD patients who are on hemodialysis throughout their lives. Patients undergoing hemodialysis can interfere with the quality of life for those undergoing it, the situation is related to the physical changes experienced by these patients. Objective: The purpose of this study was to determine the Relationship between Physical Changes and Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis at Royal Prima Hospital Medan in 2024. Methods: This study applies a quantitative research model and uses a Cross-Sectional design, where this research is a study that tries to investigate and examine how an event occurs. Results: The results of research that has been conducted on the relationship between physical changes and quality of life in Chronic kidney disease patients undergoing Hemodialysis at Royal Prima Medan Hospital, out of 32 respondents who have been studied with the Pearson Chi-Square test obtained a pvalue = 0.000 <0.05 then Ho is rejected and Ha is accepted. Conclusion: From the results, it can be concluded that there is a relationship between physical changes and quality of life in Chronic Kidney Disease patients undergoing Hemodialysis at RSU Royal Prima Medan in 2024.